2015
DOI: 10.3897/zookeys.532.5994
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Baeoura from Morocco, with a key to the West Palaearctic species (Diptera, Tipuloidea, Limoniidae)

Abstract: The genus Baeoura is represented in Morocco by two species, Baeoura ebenina Starý, 1981, and Baeoura staryi sp. n. The new species is described and illustrated, and a key to the West Palaearctic species of Baeoura is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…5). Besides the original species descriptions (Kuntze 1914;Tjeder 1974, 1976;Starý 1981;Krzemiński and Starý 1984;Mendl 1985Mendl , 1986Driauach and Belqat 2015;Hancock 2020) only few additional faunistic records are known from the Western Palearctic (Erhan-Dincă 1984;Simova-Tosic 1992;Starý and Oosterbroek 1996;Koç 2004;Ujvárosi 2005;Starý 2014;Oosterbroek et al 2020;Kolcsár et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). Besides the original species descriptions (Kuntze 1914;Tjeder 1974, 1976;Starý 1981;Krzemiński and Starý 1984;Mendl 1985Mendl , 1986Driauach and Belqat 2015;Hancock 2020) only few additional faunistic records are known from the Western Palearctic (Erhan-Dincă 1984;Simova-Tosic 1992;Starý and Oosterbroek 1996;Koç 2004;Ujvárosi 2005;Starý 2014;Oosterbroek et al 2020;Kolcsár et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Baeoura rotherayi and B. szadziewskii Krzemiński & Starý, 1984 were also collected along streams (Krzemiński and Starý 1984;Hancock 2020). Driauach and Belqat (2015) collected B. ebenina Starý, 1981 and B. staryi along partly dried out rivers, with minimal water flow in Morocco. Adults of B. alexanderi Tjeder, 1974 in Crete andB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The southern region of the Mediterranean area, including Morocco, has a special interest in nature conservation, because its geographical position, localized along the coastlines of northern Africa between the Atlantic Ocean and the Mediterranean Sea, supports high diversity ecosystems shaped by both the Mediterranean and the Saharan climate types (Abdul Malak et al 2010). Despite its geographic position, and extraordinary diversity of ecosystems, Morocco has been poorly investigated in general, especially regarding its aquatic Diptera fauna, including shortpalped craneflies, Limoniidae (Adghir et al 2018, De Jong et al 2021, Driauach et al 2013, Driauach and Belqat 2015, Driauach and Belqat 2016, Ebejer et al 2019, Eiroa et al 2020, Kettani et al 2022, Pârvu et al 2006, Pierre 1924, Savchenko et al 1992Séguy 1941a, Séguy 1941b, Starý 1971, Starý 1974, Starý 2006, Starý 2009, Starý 2011, Starý and Oosterbroek 2008, Taybi et al 2021, Vaillant 1956.…”
Section: Introductionmentioning
confidence: 99%
“…Only a single attempt was made to summarize the knowledge of the Moroccan fauna in the first checklist of the short-palped crane flies of Morocco (Driauach et al 2013) and very recent research also revealed a new species, Baeoura staryi from Morocco including an identification key of the genus Baeoura in the West Palaearctic species (Driauach and Belqat 2015). …”
Section: Introductionmentioning
confidence: 99%